Enhancing women’s resource rights for improving resilience to climate change - Monterroso, I.; Paez-Valencia A.M.; Gallagher, E.; Chesterman, Sabrina; Meinzen-Dick, Ruth S.; Enokenwa Baa, O; Elias, M. (CIFOR-ICRAF and International Fund for Agricultural Development, 2021)
This brief sets out to unpack these linkages, directly addressing two of the four COP 26 key goals, improving the ability to adapt and protect communities, in particular those more vulnerable to climate change and strengthen partnerships that mobilize knowledge and action to improve the recognition and realization of women rights.